Pedagogies magnetized by decolonial feminism in Higher Education: Study and Creation in Performing Arts (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The alliance between feminist, decolonial, and anti-racist perspectives has enabled pedagogical experiments in Higher Education that, considering the intersectionality of social markers (race, gender etc.) and the effects of the coloniality of being and knowledge, transform ways of teaching and learning. Based on debates from the Seminar Curriculum, Decoloniality, and Teacher Education at the Federal University of the State of Rio de Janeiro in 2024, and on the analysis of teaching in Performing Arts courses, using theoretical foundations and concrete methodological examples, this reflection addresses the production of embodied knowledge that seeks to re-enchant classroom practices.
Keywords: performing arts; higher education; pedagogy; feminism; decoloniality